PENGARUH INOVASI PRODUK DAN KREATIVITAS PRODUK TERHADAP MINAT BELI KONSUMEN: Studi Kasus Pada Konsumen UKM Lampu Paralon GT-Armina Surabaya - Moch Iqbal Choirudin (ECONOMOS, 2022)
This research is based on the background of innovation and creativity, many creative ideas have sprung up so that many people try to make new things as examples of used goods being used as useful goods and can be used as businesses as examples of the owner of the Paralon GT-Armina Surabaya lamp. This study aims to determine the effect of product innovation and product creativity on consumer buying interest in UKM Paralon GT-Armina lamps in Surabaya. The research design used was quantitative research. Sampling used a non-probability method, namely using Accidental Sampling, ie samples taken based on coincidences were suitable as data sources. Then the data obtained were analyzed using multiple regression analysis. This analysis includes: Validity Test, Reliability Test and Hypothesis Testing through t Test and F Test, and Coefficient of Determination (R2). The results of this study using the t-test, it can be seen that the independent variables are Product Innovation (X1) and Product Creativity (X2). The results of the F-Test value can be seen that there is a jointly significant influence between the independent variables on the dependent variable. The results of the analysis of the coefficient of determination (R Square) are known that consumer buying interest is influenced by the variables of product innovation and product creativity by 13.3%. The remaining 86.7% is influenced by other variables.